UNLOCKING SANDY OIL RESERVOIR POTENTIAL USING OPEN CELL MATRIX POLYMER (OCMP) SAND SCREEN METHOD: - Gilang Alfian Zain, Muhammad
Sand production is the phenomenon of sand particles carried by the production fluid to the surface. For many oil fields, sand production is a serious concern especially those with weakly consolidated reservoirs, sand production is a severe concern. This may lead to unfavorable consequences such as loss of well due to sand fill-up, restricted production, reduction of well productivity, detrimental damage, and/or excessive maintenance to both downhole and surface equipment, The "S" Block is an onshore field with four fields and production of about 35 MMSCFD of gas and 9,000 BPD oil from more than 670 wells. The majority of hydrocarbon accumulations are found in a sequence of upper-delta and delta-plain sandstone reservoirs from the Mid-Miocene. Before being treated by Filtrex/Open Cell Matrix Polymer (OCMP), This sandy well faced sand problems that resulted in the well producing far below its potential and eventually suffer The challenge to regain sand free production without the requirement to perform a workover can be both costly and time consuming using traditional methodologies. To address this challenge, Tendeka designed the Filtrex system, A novel remedial solution was developed to enable compliant sand free production to be restored effectively and to be compatible with thru-tubing operations, including live well deployment and single trip sand clean out. This solution includes a new filtration mechanism using an Open Cell Matrix Polymer (OCMP) filter run compressed within a sleeve to allow passage through tight restrictions which then decompresses to be conformant with a significantly larger inner diameter (ID) of the area requiring sand control when the sleeve is removed.